Níveis séricos de vitamina d e sua associação com a duração do sono em idosos: uma revisão sistemática - Lima, Karine Pereira de (2019)
The demographic and epidemiological profile has changed due to the decrease in mortality and fertility rates. Due to these events, an increasing number of elderly people are occurring, making it necessary to understand the aging process. As a consequence of aging there may be nutritional changes as the absorption of vitamins and minerals is compromised in the elderly. In the elderly, vitamin D deficiency stands out. Hypovitaminosis D in the elderly has been aggravated by the fact that they have less sun exposure and the low consumption of food sources is also related to the low serum vitamin concentrations. Aging can also affect the sleep duration of the elderly and these changes may be related to vitamin D. Therefore, the aim of this research is to evaluate the association of vitamin D with sleep duration in the elderly. It is a systematic review. Data were collected from December 2018 to March 2019, in the PubMed, Scopus, Scielo and Bireme databases. The following descriptors sleep, which is widely used in the literature and those described in the Medical Subject Headings (Mesh), were used: sleep disorders, sleep quality, vitamin D, cholecalciferol, 25 hydroxyvitamin D, aged, elderly, older with the aid of “AND ”And“ OR. In order to evaluate the methodological quality, the Newcastle Ottawa scale was used. As a result, 5 cross-sectional studies were selected, all from the pubMed database. The year 2018 appears with the largest number of articles published 60% (n = 3) and the country with the largest number of studies was South Korea 60% (n = 3). The studies classified as inadequate vitamin D <20 ng / mL or <50nmol / L and adequate> 20ng / mL and> 50 mmol / L. In order to evaluate sleep duration, the following methods were found, hours of sleep <7 or ≥7 hours, actigraphy and “how many hours of sleep per night?”. Vitamin D inadequacy was prevalent in both of genders, but when men and women were compared, women had lower vitamin D values. Elderly individuals with values below <20 ng / mL had a shorter sleep duration, whereas those values > 20ng / mL showed an improvement in sleep duration. For methodological evaluation the scores ranged from 4 to 7 points. The largest number of studies found are from South Korea, due to its geographical location, its latitude may have an influence on the low levels of vitamin D, since it is important in the formation of vitamin D. Other studies that related latitude with Vitamin D also found similar results a high prevalence of hypovitaminosis D among the elderly. The five studies revealed that there is an association between <7 hours sleep independent of the sleep duration method and vitamin D deficiency in the elderly.